EFFICIENCY OF ANTI-INFLAMMATORY THERAPY IN PATIENTS WITH ANKYLOSING SPONDYLITIS ACCORDING TO THE RESULTS OF A PROSPECTIVE FOLLOW-UP STUDY - T. A. Raskina (Научно-практическая ревматология, 2016)
In accordance  with the Ankylosing Spondylitis Assessments (ASAS) International Working Group guidelines, tumor necrosis factor-α  inhibitors are recommended in patients with ankylosing spondylitis (AS) refractory to at least two nonsteroidal  anti-inflammatory drugs (NSAIDs)  and in those with the peripheral form of the disease. Previous investigations suggest that when long used, infliximab (INF) shows a steady-state efficacy in the vast majority of patients with active AS. Works evaluating the efficiency of combined therapy using NSAIDs and INF are scarce. Objective: to evaluate the efficiency of therapy with NSAIDs and INF in patients with AS from the results of a prospective study.Subjects and methods. A total of 72 men with a valid diagnosis of AS were followed up. All the patients were allocated to two groups according to the option of basic therapy: 1) 29 patients received combined therapy with INF and NSAIDs; 2) 43 had NSAID monotherapy. Clinical, laboratory, and instrumental  examinations were performed every 12 months. Results and discussion. At 12 months of INF therapy, there were significant reductions in the values of BASDAI, BASFI, back pain, fatigue, and patient-rated global activity assessment. High BASDAI values remained in only 10 patients.At 24-month follow-up, the above measures did not significantly change as compared to the results obtained at 12 months and remained stable at 36 months. At 12 months of NSAID therapy, there were significant reductions in the values of BASDAI, back pain, fatigue, and patient-rated global activity assessment (p < 0.05). The reduction in BASFI values was insignificant. At 24 months of treatment all the measures versus those obtained after 12 months did not significantly change, except pain in the examined region of the spine, which became significantly severer than that at the 12-month follow-up. These results were also preserved at 36 months. There were more patients achieving 20% and 40% improvements and remission according to the ASAS criteria, and those with a 50% BASDAI improvement after 36 months of INF + NSAID therapy versus NSAID monotherapy (p < 0.05).Conclusion. The highest clinical effect of INF + NSAID therapy was observed within the first year and the measures in question remained stable at the 36-month follow-up after both treatments.